Concentrations of polycyclic aromatic hydrocarbons in street dust from bus stops in Qingyang city: Estimates of lifetime cancer risk and sources of exposure for daily commuters in Northwest China. (November 2020) - Wu, Yongfu; Zhang, Ning; Wang, Yingqiang; Ren, Yibin; Yuan, Zhongyu; Li, Ni
Abstract: Lifetime cancer risk and exposure of daily commuters to polycyclic aromatic hydrocarbons (PAHs) in cities of Northwest China were determined from a study of street dust samples obtained from bus stops in Qingyang city. The sum of 16 priority PAHs (Σ16 PAHs) concentrations in the dust samples ranged from 0.8 to 18.3 mg kg −1 (mean 3.0 mg kg −1 ) and the distribution of individual, carcinogenic, combustion specific, low (2–3 rings) and high molecular weight (4–6 rings) PAHs was determined. The benzo[ a ]pyrene toxic equivalents of Σ16 PAHs ranged from 0.01 to 12.2 mg kg −1 (mean 0.8 mg kg −1 ). Incremental lifetime cancer risk from exposure to PAHs in dust at bus stops in Qingyang city was estimated at 1.9 × 10 −6 for adults and 3.5 × 10 −6 for children (confidence limit ≥ 95%). Emission source analysis of PAHs in bus stop dust showed that they were mainly derived from residential coal, oil and biomass combustion, e.g. from boilers, traffic vehicles, and Kang heaters. Higher concentrations of PAHs were obtained at bus stops near transport hubs, commercial districts, and administrative institutions. Graphical abstract: Image 1 Highlights: Health risk to daily commuters from PAHs in dust at most bus stops in Qingyang was moderate. The results deserve the attention of researchers and governments in other cities. The government should try to reduce congestion of vehicle and population flow. The government should reasonably set up the number of bus lines and bus stops.